2005
DOI: 10.1634/stemcells.2004-0284
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Blood Progenitors: The Potential of These Hematopoietic Cells to Become Neural

Abstract: The mononuclear fraction from human umbilical cord blood (HUCB) contains a significant number of stem/progenitor cells that in theory could become any cell in the body, including neurons. Taking into consideration that transdifferentiation would be a very rare event and also knowing that overlapping genetic programs for hematopoiesis and neuropoiesis exist, we undertook a characterization of the HUCB mononuclear fraction, including analysis of cellular subpopulations and their morphology, cell viability, proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(60 citation statements)
references
References 44 publications
2
55
0
3
Order By: Relevance
“…In the long-term culture (60-211 days) cells expressed the early neural marker Nestin (50%) and the early neuronal marker TuJ1 (90%) which were detected immunohistochemically (Fig. 2) and confirmed by Western Blot (see [4]). However the cells expressing TuJ1 do not appear to clearly possess all of the characteristic morphology of neurons mature enough to express this marker such as the fine, long or branched processes (see Figs.…”
Section: Mononuclear Hucb Fraction Initially Consists Mostly Of Hematmentioning
confidence: 80%
See 1 more Smart Citation
“…In the long-term culture (60-211 days) cells expressed the early neural marker Nestin (50%) and the early neuronal marker TuJ1 (90%) which were detected immunohistochemically (Fig. 2) and confirmed by Western Blot (see [4]). However the cells expressing TuJ1 do not appear to clearly possess all of the characteristic morphology of neurons mature enough to express this marker such as the fine, long or branched processes (see Figs.…”
Section: Mononuclear Hucb Fraction Initially Consists Mostly Of Hematmentioning
confidence: 80%
“…Our previous experiments showed that, under culture conditions, HUCB cells are able to generate cells with neural characteristics [4]. When transplanted into the neurogenic region of neonatal rat brain, a small fraction of these cells migrate and express neuronal and astroglial proteins [46].…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation might be the increased pluripotential capability of the CB stem cell, relative to adult stem cell, with higher proliferative potentials in comparison to BM. [24][25][26] We are aware from animal studies that the addition of mesenchymal stem cells to the SCT product results in less graft rejection, due to the immunomodulating potential of these cells. 27,28 Other advantages of CB include (1) lower rates for acute GvHD and extensive chronic GvHD in comparison to unrelated donors, [29][30][31][32] (2) immediate availability, 23 reducing the period between diagnosis and SCT (in this study 7.5 months), which might improve the long-term outcome, (3) reduced likelihood of transmitting infection (viral) and (4) the suggestion that a more primitive stem cell population might have a greater capacity for transdifferentiation.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Other advantages of CB include (1) lower rates for acute GvHD and extensive chronic GvHD in comparison to unrelated donors, [29][30][31][32] (2) immediate availability, 23 reducing the period between diagnosis and SCT (in this study 7.5 months), which might improve the long-term outcome, (3) reduced likelihood of transmitting infection (viral) and (4) the suggestion that a more primitive stem cell population might have a greater capacity for transdifferentiation. [24][25][26] This latter capability might be particularly important in SCT for inborn errors of metabolism, by theoretically improving delivery of enzyme to bone, cartilage and brain tissue. More research is warranted to study this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these pluripotent mesodermal cells have recently been shown to differentiate into cells derived from other germ layers both in vitro [4] and in vivo [5]. Therefore, it is not surprising that HUCBmnf cells express numerous markers of either stemness or neural fate in vitro such as nestin, Musashi1, Oct-4, TuJ1, NCAM, A2B5, vimentin, GFAP, S100, GalC and MAP2 [6,7]. Further, these cells express neurotrophic receptors trkB, trkC and p75NTR and cytokine receptor CXCR4 [7,8].…”
Section: Introductionmentioning
confidence: 99%